Polyethylene resin composition, laminate and medical container
A tailored polyethylene resin composition with specific high-density polyethylene and ethylene polymer blends in a three-layer laminate structure addresses the challenge of maintaining transparency and heat resistance in medical containers, preventing inner layer fusion during high-temperature sterilization.
Patent Information
- Application Number
- JP2021022270
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Filing Date
- 2021-02-16
- Publication Date
- 2025-01-07
- Estimated Expiration
- 2041-02-16
AI Technical Summary
Conventional polyethylene resins used in medical containers face challenges in achieving both transparency and heat resistance, particularly during high-temperature sterilization at 126°C, and the inner layers of laminates tend to fuse or lose transparency.
A polyethylene resin composition comprising specific high-density polyethylene and ethylene polymer blends, optimized for density, melt flow rate, and molecular structure, is used in a three-layer laminate structure to maintain transparency and prevent inner layer fusion during high-temperature sterilization.
The laminate maintains excellent transparency and heat resistance, preventing inner layer fusion and ensuring peel strength below 3N/15mm after sterilization at 126°C, suitable for medical containers like infusion bags and plastic ampoules.
Smart Images

Figure 0007608856000001 
Figure 0007608856000002 
Figure 0007608856000003
Abstract
Description
[Technical field]
[0001] The present invention relates to a polyethylene resin composition, a laminate made of the composition, and a medical container using the laminate. More specifically, the present invention relates to a polyethylene resin composition that is suitable for medical containers filled with medicinal fluids, blood, etc., such as infusion bags and plastic ampoules, because it is less susceptible to loss of transparency due to high-temperature sterilization and does not cause fusion (internal fusion) between the inner layers of the laminate, and the like, and a laminate made of the composition and a medical container using the laminate. [Background technology]
[0002] Medical containers filled with medicinal fluids, blood, etc., are required to have transparency to check for contamination by foreign matter or changes due to drug compounding, heat resistance to withstand sterilization, flexibility to facilitate discharging of medicinal fluids, gas barrier properties to prevent deterioration of medicinal fluids and quality deterioration due to infiltration of water vapor and oxygen into the container, and reduction of particulate elution from the container (low particulate). Products filled with contents in these containers are generally subjected to heat sterilization. In particular, infusion preparations that are administered directly into the bloodstream are strictly required to be kept in a sterile state, and sterilization at 121°C is becoming the global standard. Among them, high-temperature sterilization at 126°C is desired to reduce the time and cost required for sterilization, and heat resistance to withstand high-temperature sterilization at 126°C is strongly required.
[0003] Conventionally, glass containers have been used as such medical containers, but due to problems such as damage to the container due to impact or dropping, and contamination due to the intrusion of outside air into the container when administering the drug solution, plastic containers that are excellent in impact resistance, flexible, and easy to drain the content liquid have come to be used. As plastic containers, soft polyvinyl chloride resin, ethylene-vinyl acetate copolymer resin, polypropylene resin, and polyethylene-based resins such as high-pressure low-density polyethylene, linear low-density polyethylene, and high-density polyethylene are used. However, soft polyvinyl chloride resins have hygiene problems such as the elution of plasticizers into the drug solution, and ethylene-vinyl acetate copolymer resins have poor heat resistance. Polypropylene is widely used as a raw material for containers that satisfy the above-mentioned transparency and heat resistance, but polypropylene has repeated tertiary carbons and is inherently prone to oxidative deterioration, so the addition of antioxidants is essential, and cleanliness is an issue. In addition, polyethylene-based resins also have problems such as a decrease in density to satisfy transparency and flexibility, which reduces heat resistance, and a decrease in transparency and flexibility, which reduces density to satisfy heat resistance.
[0004] In recent years, linear polyethylenes produced with single-site catalysts that have excellent transparency have been developed, and methods have been proposed to solve the above problems by laminating films made from these raw materials (see Patent Documents 1 to 3). However, the transparency of these laminates is still insufficient, and the impact strength of heat-sealed parts of molded containers is also not sufficient, so improvements have been desired.
[0005] Under these circumstances, in order to produce polyethylene containers that have both transparency and heat resistance, various proposals have been made, such as resin compositions and multi-layer containers whose main component is polyethylene, and even polyethylene-based resins with specific physical properties (see Patent Documents 4 to 7).
[0006] Also, a method has been proposed (see Patent Document 8) in which an inner layer, an intermediate layer, and an outer layer are laminated together, each of which is made of a material containing a polyethylene resin having specific physical properties, thereby obtaining a container that does not deform or wrinkle even after sterilization at 121°C and has excellent seal strength (see Patent Document 8). Although this method does indeed prevent the container from deforming after sterilization, it does not solve the problem of reduced transparency, and improvements have been desired.
[0007] Also, a method has been proposed in which a laminate for an infusion bag having heat resistance that allows sterilization at 124° C. is obtained by blending a specific amount of a crystal nucleating agent in an intermediate layer disposed between an outer layer and an inner layer (see Patent Document 9). However, this method does not solve the problem of reduced transparency due to sterilization treatment.
[0008] Furthermore, a method has been proposed for obtaining a laminate made of a polyethylene resin composition that does not deform and maintains high transparency even after sterilization at 121° C. (see Patent Document 10). However, as a result of further research by the present inventors, it was found that this method also has insufficient heat resistance for high-temperature sterilization at 126° C., and that the contacting parts of the container (such as the inner layers of the laminate) are fused together, and therefore improvement is necessary. [Prior art documents] [Patent documents]
[0009] [Patent Document 1] Japanese Patent Application Publication No. 8-309939 [Patent Document 2] Japanese Patent Application Publication No. 7-125738 [Patent Document 3] Japanese Patent Application Publication No. 8-244791 [Patent Document 4] JP 2002-265705 A [Patent Document 5] JP 2005-7888 A [Patent Document 6] JP 2015-42557 A [Patent Document 7] JP 2008-18063 A [Patent Document 8] JP 2003-237002 A [Patent Document 9] JP 2012-85742 A [Patent Document 10] JP 2015-096190 A Summary of the Invention [Problem to be solved by the invention]
[0010] The object of the present invention is to provide a polyethylene resin composition which has excellent heat resistance and transparency, which has been difficult to achieve in combination with conventional polyethylene resins for medical containers, and in which the inner layers of the laminate do not fuse to each other (internal fusion) even after high-temperature sterilization at 126°C, thereby maintaining high transparency; a laminate made of the composition; and a medical container using the laminate. [Means for solving the problem]
[0011] As a result of intensive research, the inventors have found that the above-mentioned problems can be solved by using a polyethylene resin composition containing a specific amount of a polyethylene resin having specific physical properties as the inner layer, or the inner layer and outer layer, of a medical container, and have thus completed the present invention.
[0012] That is, the present invention resides in the following [1] to [8]. [1] A polyethylene resin composition comprising 20 to 50% by weight of a high-density polyethylene (A) satisfying the following properties (a) to (c), and 50 to 80% by weight (the total of (A) and (B) being 100% by weight) of an ethylene polymer (B) satisfying the following properties (d) to (g), and which satisfies the following properties (h) to (i): (a) Density is 945-970 kg / m 3 It is. (b) The melt flow rate (hereinafter referred to as MFR) measured at 190° C. under a load of 21.18 N is 0.1 to 30.0 g / 10 min. (c) 13The number of hexyl or higher branches (LCB) per 1,000 carbon atoms, as determined by C-NMR spectroscopy, is less than 0.5. (d) density is 945-954 kg / m 3 It is. (e) The MFR is 0.1 to 1.0 g / 10 min. (f) In molecular weight measurement by gel permeation chromatography, the ratio of weight average molecular weight (Mw) to number average molecular weight (Mn) (Mw / Mn) is in the range of 3.0 to 5.0. (g) 13 The number of hexyl or higher branches (LCB) per 1000 carbon atoms determined from C-NMR spectroscopy is 0.5 to 2.0. (h) density is 951-957 kg / m 3 It is. (i) The MFR is 0.1 to 1.5 g / 10 min. [2] A laminate of three or more layers having at least a layer A, a layer B, and a layer C in this order, characterized in that the layer A, or the layers A and C, comprise the polyethylene resin composition described in [1] above, and the layer B comprises a thermoplastic resin. [3] The laminate according to the above [2], wherein the thermoplastic resin of layer B is a resin composition containing polyethylene. [4] A medical container comprising the laminate according to the above [2] or [3], wherein layer A is used as an inner layer. [5] A medical container having a storage section for storing a medicinal solution, wherein at least the storage section is made of the laminate described in [2] or [3] above, and the medical container described in [4] above is characterized in that layer A is an inner layer. [6] A medical container according to the above [5], characterized in that the storage section for storing the medicinal liquid is a film-like bag. [7] A medical container according to the above [5], characterized in that the container for containing the medicinal liquid is bottle-shaped. [8] A medical container according to any one of [4] to [7] above, characterized in that after sterilization at 126°C, the peel strength of the contact parts of the laminates (between the inner layers) is less than 3 N / 15 mm, and the light transmittance measured in pure water at a wavelength of 450 nm is 65% or more. Effect of the Invention
[0013] The laminate made of the resin composition of the present invention has excellent molding stability, transparency and heat resistance during water-cooled inflation molding, and further maintains its transparency even after high-temperature sterilization at 126°C and does not fuse on the inner surface. Therefore, the laminate can be suitably used for medical containers such as medical infusion bags and plastic ampoules that require high transparency and heat resistance. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0014] The polyethylene resin, resin composition, laminate made of the same, and medical container using the laminate according to the present invention will be described below. [1] High density polyethylene (A) The high density polyethylene (A) used in the present invention is an ethylene homopolymer or a copolymer of ethylene and an α-olefin.
[0015] The high density polyethylene (A) used in the present invention has an MFR of 0.1 to 30 g / 10 min, measured at 190° C. under a load of 21.18 N in accordance with JIS K6922-1. If the MFR is less than 0.1 g / 10 min, the load on the extruder increases during molding, and surface roughness and thickness unevenness in the width direction occur during molding, which is undesirable. If the MFR is more than 30 g / 10 min, the transparency decreases, which is undesirable.
[0016] High density polyethylene (A) has a density of 945 to 970 kg / m according to JIS K6922-1. 3 , preferably 950 to 965 kg / m 3 The density is 945kg / m 3 If it is less than 970kg / m, the heat resistance is insufficient and the inside surface will fuse together during high-temperature sterilization at 126℃. 3 If it exceeds this value, the transparency decreases, which is not preferable.
[0017] High density polyethylene (A) is 13The number of hexyl or more branches (LCB) per 1000 carbon atoms determined by the measurement of C-NMR spectrum is less than 0.5. If the LCB is 0.5 or more, it is not preferable because the heat resistance is insufficient, such as inner surface fusion. The high-density polyethylene (A) can be produced by, for example, a slurry method, a solution method, a gas phase method, or other production method. When producing the high-density polyethylene (A), a Ziegler catalyst consisting of a solid catalyst component containing magnesium and titanium and an organoaluminum compound, a metallocene catalyst consisting of an organic transition metal compound containing a cyclopentadienyl derivative and a compound and / or an organic metal compound that reacts with the solid catalyst component to form an ionic complex, a vanadium-based catalyst, or the like can be used, and the high-density polyethylene (A) can be produced by homopolymerizing ethylene or copolymerizing ethylene and an α-olefin using the catalyst.
[0018] The α-olefin may be any of those generally called α-olefins, and is preferably an α-olefin having 3 to 12 carbon atoms, such as propylene, butene-1, hexene-1, octene-1, 4-methyl-1-pentene, etc. Examples of copolymers of ethylene and α-olefins include ethylene-hexene-1 copolymer, ethylene-butene-1 copolymer, ethylene-octene-1 copolymer, etc.
[0019] The high density polyethylene (A) may be a commercially available product, for example, Nipolon Hard 5110, 4030 (trade name) manufactured by Tosoh Corporation.
[0020] The high density polyethylene (A) can be obtained, for example, by the method described in Japanese Patent No. 3319051. [2] Ethylene-based polymer (B) The ethylene polymer (B) used in the present invention has an MFR of 0.1 to 1.0 g / 10 min, measured at 190° C. and a load of 21.18 N according to JIS K6922-1. If the MFR is less than 0.1 g / 10 min, the load on the extruder increases during molding, and surface roughness and thickness unevenness in the width direction occur during molding, which is undesirable. If the MFR is more than 1.0 g / 10 min, the transparency decreases, which is undesirable.
[0021] The ethylene polymer (B) has a density of 945 to 954 kg / m according to JIS K6922-1. 3 The density is 945kg / m 3 If it is less than 954kg / m, the heat resistance is insufficient and the inside surface will fuse together during high-temperature sterilization at 126℃. 3 If it exceeds this value, the transparency decreases, which is not preferable.
[0022] In addition, the ratio (Mw / Mn) of the weight average molecular weight (Mw) to the number average molecular weight (Mn) in molecular weight measurement by gel permeation chromatography (hereinafter referred to as GPC) is in the range of 3.0 to 5.0, and preferably in the range of 3.5 to 4.5. 13 The number of hexyl or higher branched groups (LCB) per 1000 carbon atoms, as determined by C-NMR spectroscopy, is 0.5 to 2. If Mw / Mn is less than 3.0, the transparency decreases, and if it exceeds 5.0, the transparency also decreases, which is not preferable. If the LCB is less than 0.5, the transparency decreases, and if it exceeds 2, industrial production is difficult.
[0023] The ethylene polymer (B) is produced using a metallocene catalyst. The metallocene catalyst used has one metallocene complex, an activating cocatalyst, and, if necessary, an organoaluminum compound as constituent components, and it is preferable to carry out copolymerization of the macromonomer with ethylene, or of the macromonomer with ethylene and an olefin having 3 to 6 carbon atoms, simultaneously with the synthesis of the macromonomer. The macromonomer is an olefin polymer having a vinyl group at the end, and is an ethylene polymer having a vinyl group at the end obtained by homopolymerizing ethylene or copolymerizing ethylene with an olefin having 3 to 6 carbon atoms. As the metallocene complex of the metallocene catalyst for synthesizing the macromonomer and copolymerizing the macromonomer with ethylene, or the macromonomer with ethylene and an olefin having 3 to 6 carbon atoms, a catalyst using a non-bridged bis(indenyl)zirconium complex, a non-bridged bis(cyclopentadienyl)zirconium complex, a bridged bis(cyclopentadienyl)zirconium complex, a bridged bis(indenyl)zirconium complex, a bridged (cyclopentadienyl)(indenyl)zirconium complex, a bridged (cyclopentadienyl)(fluorenyl)zirconium complex or a bridged (indenyl)(fluorenyl)zirconium complex is preferred. Specific examples of metallocene complexes include bis(indenyl)zirconium dichloride, dimethylsilanediylbis(cyclopentadienyl)zirconium dichloride, dimethylsilanediyl(cyclopentadienyl)(indenyl)zirconium dichloride, dimethylsilanediyl(cyclopentadienyl)(2-methylindenyl)zirconium dichloride, dimethylsilanediyl(cyclopentadienyl)(4,7-dimethylindenyl)zirconium dichloride, and dimethylsilanediyl(cyclopentadienyl)(2,4,7-dimethylindenyl)zirconium dichloride. Examples of the dichlorides include diphenylmethylene(1-cyclopentadienyl)(9-fluorenyl)zirconium dichloride, diphenylmethylene(1-cyclopentadienyl)(2,7-di-t-butyl-9-fluorenyl)zirconium dichloride, and isopropylidene(1-cyclopentadienyl)(2,7-di-t-butyl-9-fluorenyl)zirconium dichloride, as well as the dimethyl, diethyl, dihydro, diphenyl, and dibenzyl forms of the above transition metal compounds. In addition, compounds in which the zirconium atom of the above transition metal compound is replaced with a titanium atom or a hafnium atom can also be exemplified, but are not limited to these. Of these, one or more types may be used, but it is particularly preferable to use one type.
[0024] The activating cocatalyst used as a component of the metallocene catalyst refers to a compound that plays a role in converting a metallocene complex or a reaction product of a metallocene complex and an organoaluminum compound into an active species capable of polymerizing an olefin, and is preferably a compound that generates a cationic compound from the metallocene complex, and the generated cationic compound acts as a polymerization active species capable of polymerizing an olefin. The activating cocatalyst is a compound that provides a compound that, after forming a polymerization active species, weakly coordinates or interacts with the generated cationic compound but does not directly react with the active species.
[0025] Specific examples of the activating cocatalyst include boron compounds such as alkylaluminoxanes such as methylaluminoxane, alkylaluminoxanes supported on silica gel, tris(fluorinated aryl)borons such as tris(pentafluorophenyl)boron, and tetrakis(fluorinated aryl)boron salts such as N,N-dimethylammonium-tetrakis(pentafluorophenyl)boron, as well as silica gel-supported versions of these, as well as clay minerals and clay minerals treated with organic compounds. Of these activating cocatalysts, it is preferable to use clay minerals treated with organic compounds.
[0026] When a clay mineral treated with an organic compound is used as an activating cocatalyst, the clay mineral used is preferably a clay mineral belonging to the smectite group, specific examples of which include montmorillonite, beidellite, saponite, hectorite, etc. In addition, a mixture of a plurality of these clay minerals can be used.
[0027] The organic compound treatment refers to the introduction of organic ions between clay mineral layers to form an ion complex. Examples of organic compounds used in the organic compound treatment include alkyl ammonium salts such as N,N-dimethyl-n-octadecylamine hydrochloride, N,N-dimethyl-n-eicosylamine hydrochloride, N,N-dimethyl-n-docosylamine hydrochloride, N,N-dimethyloleylamine hydrochloride, N,N-dimethylbehenylamine hydrochloride, N-methyl-bis(n-octadecyl)amine hydrochloride, N-methyl-bis(n-eicosyl)amine hydrochloride, N-methyl-dioleylamine hydrochloride, N-methyl-dibehenylamine hydrochloride, and N,N-dimethylaniline hydrochloride.
[0028] There is no particular limitation on the method for preparing the metallocene catalyst, such as a method of reacting a metallocene complex with an activating cocatalyst.
[0029] When preparing the metallocene catalyst, an alkylaluminum such as triethylaluminum or triisobutylaluminum may be used as necessary for activating the metallocene complex or removing impurities in the solvent.
[0030] When producing the ethylene polymer (B), the polymerization temperature is preferably −100 to 120° C., and particularly in consideration of productivity, the polymerization temperature is preferably 20 to 120° C., and more preferably 60 to 120° C. The polymerization time is preferably in the range of 10 seconds to 20 hours, and the polymerization pressure is preferably in the range of normal pressure to 300 MPa.
[0031] The polymerizable monomers are ethylene and an α-olefin having 3 to 6 carbon atoms, and the supply ratio of the ethylene and the α-olefin having 3 to 6 carbon atoms can be such that the α-olefin having 3 to 6 carbon atoms / ethylene (molar ratio) is 0 to 0.2, preferably 0 to 0.15. It is also possible to adjust the molecular weight by using hydrogen or the like during polymerization. In this case, the amount of hydrogen used can be such that the hydrogen / ethylene (molar ratio) is 0 to 0.002 (hydrogen concentration: 2,000 ppm), preferably 0 to 0.0005 (hydrogen concentration: 500 ppm).
[0032] The polymerization can be carried out by any of batch, semi-continuous, and continuous methods, and can also be carried out in two or more stages by changing the polymerization conditions. After the polymerization is completed, the ethylene-α-olefin copolymer can be separated and recovered from the polymerization solvent by a conventionally known method, and then dried to obtain the copolymer. The polymerization can be carried out in a slurry state, a solution state, or a gas phase state, and in particular, when the polymerization is carried out in a slurry state, an ethylene-based polymer having a regular powder particle shape can be efficiently and stably produced. The ethylene-based polymer (B) can be obtained by a known method such as that described in JP2011-105934A. [3] Polyethylene resin composition The polyethylene resin composition, which is one embodiment of the present invention, can be obtained by mixing the above-mentioned high-density polyethylene (A) and ethylene polymer (B) by a conventionally known method, for example, a method using a Henschel mixer, a V-blender, a ribbon blender, a tumbler blender or the like, or by further melt-kneading a mixture obtained by such a method using a single-screw extruder, a twin-screw extruder, a kneader, a Banbury mixer or the like, and then granulating the mixture.
[0033] The blending ratio of the high density polyethylene (A) and the ethylene polymer (B) is 20-50% by weight of the high density polyethylene (A) and 50-80% by weight of the ethylene polymer (B). If the high density polyethylene (A) is less than 20% by weight, the heat resistance of the resulting laminate is insufficient and inner surface fusion occurs, and if it exceeds 50% by weight, the transparency of the resulting laminate decreases, which is not preferable. If the ethylene polymer (B) is less than 50% by weight, the transparency of the resulting laminate decreases, and if it exceeds 80% by weight, the heat resistance of the resulting laminate is insufficient and inner surface fusion occurs, which is not preferable.
[0034] The resin composition of the present invention has an MFR of 0.1 to 1.5 g / 10 min and a density of 951 to 957 kg / m 3 When the MFR is in the range, the molding stability is good, the transparency after high-temperature sterilization at 126° C. is excellent, and no inner surface fusion occurs, which is preferable. When the MFR is less than 0.1 g / 10 min, the extrusion properties decrease, which is unpreferable, and when the MFR exceeds 1.5 g / 10 min, the transparency decreases, which is unpreferable.
[0035] When the ethylene-based polymer (B) is blended within the above range in the laminate which is one embodiment of the present invention, it becomes possible to maintain a high level of transparency even after sterilization treatment, compared with a case in which the ethylene-based polymer (B) is not blended.
[0036] To the polyethylene resin composition which is one embodiment of the present invention, commonly used known additives such as antioxidants, antistatic agents, lubricants, antiblocking agents, antifogging agents, organic or inorganic pigments, ultraviolet absorbers, dispersants, etc. may be appropriately blended as necessary within the scope of not significantly impairing the effects of the present invention. The method for blending the above-mentioned additives in the resin composition according to the present invention is not particularly limited, but examples thereof include a method of directly adding the additives in the pelletizing step after polymerization, and a method of preparing a high-concentration master batch in advance and dry-blending this at the time of molding.
[0037] The polyethylene resin composition may also be blended with other thermoplastic resins such as polypropylene, ethylene-propylene copolymer rubber, poly-1-butene, etc., within the range that does not impair the effects of the present invention. [4] Laminate A laminate according to one embodiment of the present invention is a laminate of three or more layers having at least a layer A, a layer B, and a layer C in this order, in which layer A or layer A and layer C are made of the following polyethylene resin composition, and layer B is made of a thermoplastic resin.
[0038] A polyethylene resin composition comprising 20 to 50% by weight of a high-density polyethylene (A) satisfying the following properties (a) to (c), and 50 to 80% by weight (the total of (A) and (B) being 100% by weight) of an ethylene polymer (B) satisfying the following properties (d) to (g), and which satisfies the following properties (h) to (i): (a) Density is 945-970 kg / m 3 It is. (b) The MFR is 0.1 to 30.0 g / 10 min. (c) 13 The number of hexyl or higher branches (LCB) per 1,000 carbon atoms, as determined by C-NMR spectroscopy, is less than 0.5. (d) density is 945-954 kg / m 3 It is. (e) The MFR is 0.1 to 1.0 g / 10 min. (f) In molecular weight measurement by gel permeation chromatography, the ratio of weight average molecular weight (Mw) to number average molecular weight (Mn) (Mw / Mn) is in the range of 3.0 to 5.0. (g) 13 The number of hexyl or higher branches (LCB) per 1000 carbon atoms determined from C-NMR spectroscopy is 0.5 to 2.0. (h) density is 951-957 kg / m 3 It is. (i) The MFR is 0.1 to 1.5 g / 10 min.
[0039] The blending ratio of the high density polyethylene (A) and the ethylene polymer (B) in layers A and C may be the same or different so long as it is within the above range.
[0040] The thermoplastic resin used in the B layer is not particularly limited, but it is preferable to use a resin that has an excellent balance between transparency and heat resistance. For example, a resin composition containing polyethylene can be mentioned, and as the polyethylene, FY12 and FY14 (trade name) manufactured by Tosoh Corporation are suitable from the viewpoint of transparency and heat resistance. In addition, resins other than polyethylene, such as polypropylene, may be used in the B layer as long as the effect of the present invention is not impaired.
[0041] The thermoplastic resin used in the layer B can be obtained by, for example, the method described in JP-A-2015-096190.
[0042] The laminate of the present invention is not particularly limited in terms of the other layer configurations, so long as it has the A layer, the B layer, and the C layer (the A layer is a heat seal layer) in this order. The number of layers is most preferably three layers consisting of the A layer / B layer / C layer, but is not limited thereto. The A layer / B layer / C layer structure may have a layer A / B layer / center layer / B layer / C layer in which a layer is further formed within the B layer, or other layers may be provided between the B layer and the C layer or between the A layer and the B layer as necessary. Examples of such other layers include an adhesive layer, a gas barrier layer, and an ultraviolet absorbing layer. For example, a five-layer structure such as the A layer / adhesive layer / B layer / gas barrier layer / C layer may be used. A new layer may also be provided outside the C layer. The symbol / between layers indicates that the layers are adjacent.
[0043] Examples of adhesives constituting the adhesive layer include polyurethane adhesives, vinyl acetate adhesives, hot melt adhesives, or adhesive resins such as maleic anhydride modified polyolefins, ionomer resins, etc. When an adhesive layer is included in the layer structure, the essential constituent layers such as layer A, layer B, and layer C can be laminated by co-extrusion with these adhesives.
[0044] The total thickness of the laminate in the present invention is not particularly limited and can be appropriately determined as necessary, but is preferably 0.01 to 1 mm, more preferably 0.1 to 0.5 mm.
[0045] Although the thickness ratio of each layer is not particularly limited, it is preferable to make the thickness of layers C and A, which have high density to prevent deformation or fusion due to sterilization treatment, etc., thin, and to make the thickness of layer B, which has low density to increase transparency, thick, because this improves the balance between transparency and heat resistance. The thickness ratio of each layer is preferably about A layer:B layer:C layer = 1 to 30:40 to 98:1 to 30 (however, the total is 100).
[0046] The laminate of the present invention is subjected to high-temperature sterilization treatment at 126°C for 20 minutes, and from the viewpoint of transparency, it is preferable that the light transmittance after sterilization is 65% or more, and from the viewpoint of heat resistance, it is preferable that the peel strength of the contact parts between the inner layers of the laminate is less than 3 N / 15 mm and that no fusion (internal fusion) occurs.
[0047] The method for producing the laminate of the present invention is not particularly limited, but includes methods for forming a multilayer film or sheet by a water-cooled or air-cooled coextrusion multilayer inflation method, a coextrusion multilayer T-die method, a dry lamination method, an extrusion lamination method, etc. Among these, it is preferable to use a water-cooled coextrusion multilayer inflation method or a coextrusion multilayer T-die method. In particular, when the water-cooled coextrusion multilayer inflation method is used, there are many advantages in terms of transparency, hygiene, etc. In addition, the laminate may be molded into a bottle shape by a multilayer blow molding method. [5] Medical containers A medical container according to one embodiment of the present invention is made of the laminate and has layer A as an inner layer. Another embodiment of the present invention is a medical container having a storage section for storing a medicinal solution, at least the storage section is made of the laminate and has layer A as an inner layer.
[0048] The medical container of the present invention is subjected to high-temperature sterilization treatment at 126°C for 20 minutes. From the viewpoint of transparency, it is preferable that the light transmittance after sterilization is 65% or more, and from the viewpoint of heat resistance, it is preferable that the peel strength of the contact parts between the inner layers of the laminate is less than 3 N / 15 mm and that no fusion (internal fusion) occurs.
[0049] The shape of the container that contains the liquid medicine can be, for example, a film bag or a bottle.
[0050] When the laminate is formed into a film by a water-cooled or air-cooled coextrusion multilayer inflation method, a coextrusion multilayer T-die method, a dry lamination method, an extrusion lamination method, or the like, two sheets of the obtained film are stacked and the periphery is heat-sealed to form a bag-shaped storage section. The obtained film can also be formed into a recessed portion to be the storage section by hot plate forming such as vacuum forming or pressure forming, and then stacked so that the recessed portions face each other and the periphery is heat-sealed to form the storage section. In this case, the port portion to be the inlet and outlet of the drug solution may be formed by heat sealing at the same time as the formation of the storage section, or the formation of the storage section and the formation of the port portion can be performed in separate steps. The laminate can also be formed into a bottle by a multilayer blow molding method or the like to form the storage section. In multilayer blow molding, a parison made of the laminate is extrusion-molded, the parison is sandwiched between dies, and clean air is blown into the parison to form a bottle-shaped storage section. The port portion can be formed by using a mold for integral molding with the storage portion, by heat sealing the port portion to the storage portion, or by insert blow molding to integrate the port portion with the storage portion at the same time as molding it.
[0051] The polyethylene medical container of the present invention can be used in general medical applications, such as blood bags, platelet storage bags, infusion (medicinal solution) bags, medical multi-chamber containers, artificial dialysis bags, eye drop containers, and injection ampoules. EXAMPLES
[0052] The present invention will be described in more detail below by showing examples, but the present invention is not limited to these examples. A. Resin The properties of the resins used in the examples and comparative examples were evaluated by the following methods.
[0053] <density> The density was measured by a density gradient tube method in accordance with JIS K6922-1.
[0054] <mfr> The MFR (melt flow rate) was measured in accordance with JIS K6922-1.
[0055] <Molecular weight, molecular weight distribution> Weight average molecular weight (Mw), number average molecular weight (Mn), and the ratio of weight average molecular weight to number average molecular weight (Mw / Mn) were measured by GPC. A GPC device (Tosoh Corporation (trade name) HLC-8121GPC / HT) and a column (Tosoh Corporation (trade name) TSKgel GMHhr-H(20)HT) were used, the column temperature was set to 140°C, and 1,2,4-trichlorobenzene was used as the eluent. The measurement sample was prepared at a concentration of 1.0 mg / ml, and 0.3 ml was injected for measurement. The molecular weight calibration curve was calibrated using a polystyrene sample with a known molecular weight. Note that Mw and Mn were calculated as values converted into linear polyethylene.
[0056] <Long chain branching> The number of long chain branches per 1000 carbon atoms was measured by carbon nuclear magnetic resonance ( 13 The carbon nuclear magnetic resonance (C-NMR) method was used to measure the carbon 13 The C-NMR spectrum was measured, and the number of long chain branches per 1000 carbon atoms in the polymer was calculated using the following calculation method. The measurement temperature was set at 130°C, and a mixed solution of 1,2-dichlorobenzene / 1,2-dichlorobenzene-d4 = 75 / 25 (volume ratio) was used as the solvent. <How to calculate the number of long chain branches (LCB)> In the NMR spectrum with a Gaussian window function, the sum of the peak areas of all peaks having a peak top at 5 to 50 ppm was set to 1000, and the number of long chain branches (the number of branches having 7 or more carbon atoms) was calculated from the peak area of the peak derived from the methine carbon bonded with a branch having 7 or more carbon atoms. Under these measurement conditions, the number of long chain branches (the number of branches having 7 or more carbon atoms) was calculated from the peak area of the peak having a peak top near 38.22 to 38.27 ppm. The peak area of the peak was taken as the area of the signal in the range from the chemical shift of the valley with the adjacent peak on the high magnetic field side to the chemical shift of the valley with the adjacent peak on the low magnetic field side. In addition, under these measurement conditions, the peak top position of the peak derived from the methine carbon bonded with the hexyl branch was 38.21 ppm in the measurement of the ethylene-1-octene copolymer.
[0057] In the examples and comparative examples, resins produced by the following methods and commercially available products were used. (1) High-density polyethylene A-1: The following commercially available products were used.
[0058] Tosoh Corporation, (product name) Nipolon Hard 5110 (MFR = 0.9 g / 10 min, density = 961 kg / m 3 The results of the evaluation of the basic characteristics of A-1 are shown in Table 1.
[0059] A-2: The following commercially available products were used.
[0060] Tosoh Corporation, (product name) Nipolon Hard 4030 (MFR = 5.0 g / 10 min, density = 965 kg / m 3 The results of the evaluation of the basic characteristics of A-2 are shown in Table 1.
[0061] A-3: The following commercially available products were used.
[0062] Tosoh Corporation, (product name) Nipolon Hard 1000 (MFR = 20g / 10min, density = 964kg / m 3 The results of the evaluation of the basic characteristics of A-3 are shown in Table 1.
[0063] A-4 [[Preparation of organically modified clay] In a 1-liter flask, 300 ml of industrial alcohol (product name Ekinen F-3, manufactured by Japan Alcohol Sales Co., Ltd.) and 300 ml of distilled water were added, and 15.0 g of concentrated hydrochloric acid and dioleylmethylamine ((C 18 H 35 )2(CH3)N, 63.7g (120mmol) of (Lipomin MO, manufactured by Lion Specialty Chemicals Co., Ltd.) was added and heated to 45℃, after which 100g of synthetic hectorite (Laponite RD, manufactured by BYK Co., Ltd.) was dispersed, and the temperature was raised to 60℃ and stirred for 1 hour while maintaining the temperature. After filtering the slurry, it was washed twice with 600ml of water at 60℃ and dried in a dryer at 85℃ for 12 hours to obtain 130g of organically modified clay. This organically modified clay was pulverized in a jet mill to a median diameter of 15μm. [Preparation of polymerization catalyst] After replacing the air in a 300mL flask equipped with a thermometer and reflux condenser with nitrogen, 25.0g of the organically modified clay obtained in [Preparation of organically modified clay] and 108mL of hexane were added, followed by the addition of 0.392g (1mmol) of bis(indenyl)zirconium dichloride and 142mL of 20% triisobutylaluminum, and stirring for 3 hours at 60°C. After cooling to room temperature, the supernatant was removed and washed twice with 220mL of hexane, and then 220mL of hexane was added to obtain a catalyst suspension (solid weight content: 12.0wt%). [Production of A-4] A 2-liter autoclave was charged with 1.2 liters of hexane, 1.0 mL of 20% triisobutylaluminum, and 200 mg (equivalent to 24 mg of solids) of the catalyst suspension obtained in [Preparation of polymerization catalyst]. The temperature was raised to 85°C, and then ethylene / hydrogen mixed gas was continuously fed so that the partial pressure was 0.90 MPa (hydrogen concentration in ethylene / hydrogen mixed gas: 450 ppm). After 90 minutes, the pressure was released, and the slurry was filtered and dried to obtain 205 g of polymer. The MFR of this polymer was 1.0 g / 10 min, and the density was 952 kg / m 3 The results of the evaluation of the basic characteristics of A-4 are shown in Table 1.
[0064] [Table 1]
[0065] (2) Ethylene-based polymers B-1 [Preparation of denatured clay] 300 mL of industrial alcohol (trade name: Ekinen F-3, manufactured by Japan Alcohol Sales Co., Ltd.) and 300 mL of distilled water were placed in a 1 L flask, 15.0 g of concentrated hydrochloric acid and 42.4 g (120 mmol) of dimethylbehenylamine (trade name: Armin DM22D, manufactured by Lion Corporation) were added, and the mixture was heated to 45 ° C. to disperse 100 g of synthetic hectorite (trade name: Laponite RDS, manufactured by Rockwood Additives Co., Ltd.), and then heated to 60 ° C. and stirred for 1 hour while maintaining the temperature. After filtering the slurry, it was washed twice with 600 mL of water at 60 ° C. and dried in a dryer at 85 ° C. for 12 hours to obtain 122 g of organically modified clay. This organically modified clay was spray-dried to a median diameter of 15 μm. [Preparation of polymerization catalyst] After replacing the air in a 300mL flask equipped with a thermometer and reflux condenser with nitrogen, 25.0g of the organically modified clay obtained in (1) and 108mL of hexane were added, followed by the addition of 0.4406g of dimethylsilylene(cyclopentadienyl)(2,4,7-trimethyl-1-indenyl)zirconium dichloride and 142mL of 20% triisobutylaluminum, and stirring for 3 hours at 60°C. After cooling to 45°C, the supernatant was removed and washed five times with 200mL of hexane, and 200mL of hexane was added to obtain a catalyst suspension (solid weight content: 12.0wt%). [Production of B-1] In a 2L autoclave, 1.2L of hexane, 1.0mL of 20% triisobutylaluminum, and 358mg (equivalent to 43mg of solids) of the catalyst suspension obtained in [Preparation of polymerization catalyst] were added, and after heating to 70°C, 1.2g of 1-butene was added, and ethylene / hydrogen mixed gas was continuously fed so that the partial pressure was 0.80MPa (hydrogen concentration in ethylene / hydrogen mixed gas: 765ppm). After 90 minutes, the pressure was released, and the slurry was filtered and dried to obtain 65g of polymer. The MFR of this polymer was 0.4g / 10min, and the density was 947kg / m 3 The number average molecular weight (Mn) was 3.2 × 10 4 , weight average molecular weight is 13.0 × 10 4 The Mw / Mn was 4.1, and the number of long chain branches contained in the polymer was 0.8 per 1000 carbon atoms in the main chain. The results of the evaluation of the basic properties of B-1 are shown in Table 2.
[0066] B-2 [Preparation of denatured clay] A modified clay compound was prepared in the same manner as in B-1. [Preparation of polymerization catalyst] A polymerization catalyst was prepared in the same manner as in B-1. [Production of B-2] In a 2L autoclave, 1.2L of hexane, 1.0mL of 20% triisobutylaluminum, and 358mg (equivalent to 43mg of solids) of the catalyst suspension obtained in [Preparation of polymerization catalyst] were added, and the temperature was raised to 70°C. Then, 4.6g of 1-butene was added, and ethylene / hydrogen mixed gas was continuously fed so that the partial pressure was 0.80MPa (hydrogen concentration in ethylene / hydrogen mixed gas: 1600ppm). After 90 minutes, the pressure was released, and the slurry was filtered and dried to obtain 86g of polymer. The MFR of this polymer was 2.0g / 10min, and the density was 941kg / m 3 The number average molecular weight (Mn) was 2.0×10 4 , weight average molecular weight is 9.5 × 10 4 The Mw / Mn was 4.5, and the number of long chain branches contained in the polymer was 1.6 per 1000 carbon atoms in the main chain. The results of the evaluation of the basic properties of B-2 are shown in Table 2.
[0067] B-3 [Preparation of denatured clay] A modified clay compound was prepared in the same manner as in B-1. [Preparation of polymerization catalyst] A polymerization catalyst was prepared in the same manner as in B-1. [Production of B-3] In a 2L autoclave, 1.2L of hexane, 1.0mL of 20% triisobutylaluminum, and 358mg (equivalent to 43mg of solids) of the catalyst suspension obtained in [Preparation of polymerization catalyst] were added, and after heating to 70°C, 2.9g of 1-butene was added, and ethylene / hydrogen mixed gas was continuously fed so that the partial pressure was 0.80MPa (hydrogen concentration in ethylene / hydrogen mixed gas: 1260ppm). After 90 minutes, the pressure was released, and the slurry was filtered and dried to obtain 68g of polymer. The MFR of this polymer was 1.0g / 10min, and the density was 945kg / m 3 The number average molecular weight (Mn) was 2.4 × 10 4 , the weight average molecular weight is 10.3 × 10 4 The Mw / Mn was 4.3, and the number of long chain branches contained in the polymer was 0.8 per 1000 carbon atoms in the main chain. The results of the evaluation of the basic properties of B-3 are shown in Table 2.
[0068] B-4 [Preparation of denatured clay] A modified clay compound was prepared in the same manner as in B-1. [Preparation of polymerization catalyst] A polymerization catalyst was prepared in the same manner as in B-1. [Production of B-4] In a 2L autoclave, 1.2L of hexane, 1.0mL of 20% triisobutylaluminum, and 358mg (equivalent to 43mg of solids) of the catalyst suspension obtained in [Preparation of polymerization catalyst] were added, and after heating to 70°C, 0.7g of 1-butene was added, and ethylene / hydrogen mixed gas was continuously fed so that the partial pressure was 0.80MPa (hydrogen concentration in ethylene / hydrogen mixed gas: 850ppm). After 90 minutes, the pressure was released, and the slurry was filtered and dried to obtain 110g of polymer. The MFR of this polymer was 1.0g / 10min, and the density was 951kg / m 3 The number average molecular weight (Mn) was 2.6 × 10 4 , the weight average molecular weight is 10.7 × 10 4 The Mw / Mn was 4.1, and the number of long chain branches contained in the polymer was 1.0 per 1000 carbon atoms in the main chain. The results of the evaluation of the basic properties of B-4 are shown in Table 2.
[0069] B-5 [Preparation of denatured clay] A modified clay compound was prepared in the same manner as in B-1. [Preparation of polymerization catalyst] A polymerization catalyst was prepared in the same manner as in B-1. [Production of B-5] In a 2L autoclave, 1.2L of hexane, 1.0mL of 20% triisobutylaluminum, and 358mg (equivalent to 43mg of solids) of the catalyst suspension obtained in [Preparation of polymerization catalyst] were added, and the temperature was raised to 70°C. Then, ethylene / hydrogen mixed gas was continuously fed so that the partial pressure was 0.80MPa (hydrogen concentration in ethylene / hydrogen mixed gas: 2000ppm). After 90 minutes, the pressure was released, and the slurry was filtered and dried to obtain 291g of polymer. The MFR of this polymer was 2.0g / 10min, and the density was 958kg / m 3 The number average molecular weight (Mn) was 2.0×10 4 , weight average molecular weight is 9.1 × 10 4 The Mw / Mn ratio was 4.5, and the number of long chain branches contained in the polymer was 1.5 per 1000 carbon atoms in the main chain.
[0070] The results of the basic characteristic evaluation of B-5 are shown in Table 2.
[0071] B-6 [Preparation of denatured clay] A modified clay compound was prepared in the same manner as in B-1. [Preparation of polymerization catalyst] A polymerization catalyst was prepared in the same manner as in B-1. [Production of B-6] A 2L autoclave was charged with 1.2L of hexane, 1.0mL of 20% triisobutylaluminum, and 358mg (equivalent to 43mg of solids) of the catalyst suspension obtained in [Preparation of polymerization catalyst], and the temperature was raised to 70°C. Then, ethylene / hydrogen mixed gas was continuously fed so that the partial pressure was 0.80MPa (hydrogen concentration in ethylene / hydrogen mixed gas: 843ppm). After 90 minutes, the pressure was released, and the slurry was filtered and dried to obtain 291g of polymer. The MFR of this polymer was 0.2g / 10min, and the density was 941kg / m 3 The number average molecular weight (Mn) was 2.8 × 10 4 , weight average molecular weight is 11.0 × 10 4 The Mw / Mn was 4.0, and the number of long chain branches contained in the polymer was 1.0 per 1000 carbon atoms in the main chain.
[0072] The results of the basic characteristic evaluation of B-6 are shown in Table 2.
[0073] [Table 2]
[0074] <Resin composition> The high density polyethylene (A) and the ethylene polymer (B) were dry blended in the ratios described in the Examples and Comparative Examples. B. Laminates and sealed containers The laminates and medical containers used in the examples and comparative examples were produced and sterilized by the following methods.
[0075] <Production of Laminate and Medical Container> A three-layer water-cooled inflation molding machine (Placo) was used to mold a three-layer film with a width of 135 mm and a thickness of 250 μm at a cylinder temperature of 180°C, a water bath temperature of 15°C, and a take-up speed of 6 m / min. The middle layer was made of polyethylene (product name) Nipolon-P FY12 (MFR = 1.7 g / 10 min, density = 916 kg / m) manufactured by Tosoh Corporation. 3 ) was used. The thickness of each layer was molded so that the outer and inner layers were 20 μm, and the middle layer was 210 μm. Next, a sample with a length of 195 mm was cut out from the three-layer film, one end was heat-sealed to form a bag, which was then filled with 300 ml of ultrapure water and heat-sealed with a head space of 50 ml to produce a medical container. Furthermore, a sample with a length of 180 mm was cut out from the three-layer film, one end was heat-sealed to form a bag, which was then inserted with a release film with a width of 80 mm and a length of 170 mm, and vacuum-packed to produce a tightly sealed container.
[0076] <Sterilization process> The medical container was sterilized at 126° C. for 20 minutes using a steam sterilizer (manufactured by Hisaka Works, Ltd.).
[0077] The properties of the resin compositions, laminates, and medical containers used in the examples and comparative examples were evaluated by the following methods.
[0078] <Transparency> Test pieces measuring 10 mm wide x 50 mm long were cut from the three-layer film and the sterilized medical container, and the light transmittance at a wavelength of 450 nm was measured in pure water using an ultraviolet-visible spectrophotometer (Model V-730, manufactured by JASCO Corp.) A medical container with good transparency was determined to have a light transmittance of 65% or more maintained after sterilization.
[0079] <Inner fusion adhesion (heat resistance)> Test pieces measuring 15 mm wide x 100 mm long were cut from the three-layer film and the sealed container after sterilization, and the peel strength was measured using a tensile tester (model RTE-1210, manufactured by Orientec Co., Ltd.) A peel strength of less than 3 N / 15 mm maintained after sterilization was considered to be an indicator of a good medical container that was not fused to the inside.
[0080] Example 1 Using the resin composition shown in Table 3, a three-layer film was molded using a water-cooled inflation molding machine, and the molding stability, surface smoothness, and transparency of the film were evaluated. The thickness of the film was 250 μm. Next, the obtained film was heat-sealed, and a medical container filled with ultrapure water and the obtained film were heat-sealed to prepare a sealed container with a release sheet inserted therein. The containers were sterilized by high-pressure steam at 126°C, and the transparency and inner surface fusion property after sterilization were evaluated. The evaluation results are shown in Table 4.
[0081] Examples 2 to 9, Comparative Examples 1 to 12 A three-layer film, a medical container, and a tightly sealed container were produced and evaluated in the same manner as in Example 1, except that the resin compositions used for the inner and outer layers were changed as shown in Tables 3 and 4. The evaluation results are shown in Tables 5 and 6.
[0082] [Table 3]
[0083] [Table 4]
[0084] [Table 5]
[0085] [Table 6] < / mfr>
Claims
1. A polyethylene resin composition comprising 20 to 50% by weight of a high-density polyethylene (A) satisfying the following properties (a) to (c), and 50 to 80% by weight (the total of (A) and (B) being 100% by weight) of an ethylene-based polymer (B) satisfying the following properties (d) to (g), and which satisfies the following properties (h) to (i): (a) Density is 945 to 970 kg / m 3 It is. (b) The melt flow rate (hereinafter referred to as MFR) measured at 190° C. under a load of 21.18 N is 0.1 to 30.0 g / 10 min. (c) 13 The number of hexyl or higher branches (LCB) per 1,000 carbon atoms, as determined by C-NMR spectroscopy, is less than 0.
5. (d) density is 945 to 954 kg / m 3 It is. (e) The MFR is 0.1 to 1.0 g / 10 min. (f) In the molecular weight measurement by gel permeation chromatography, the ratio (Mw / Mn) of the weight average molecular weight (Mw) to the number average molecular weight (Mn) is in the range of 3.0 to 5.
0. (g) 13 The number of hexyl or higher branches (LCB) per 1,000 carbon atoms, as determined by C-NMR spectroscopy, is 0.5 to 2.
0. (h) density is 951 to 957 kg / m 3 It is. (i) The MFR is 0.1 to 1.5 g / 10 min.
2. A laminate of three or more layers having at least a layer A, a layer B and a layer C in this order, wherein the layer A or the layers A and C comprise the polyethylene resin composition according to claim 1, and the layer B comprises a thermoplastic resin.
3. 3. The laminate according to claim 2, wherein the thermoplastic resin of the layer B is a resin composition containing polyethylene.
4. 4. A medical container comprising the laminate according to claim 2 or 3, with layer A serving as an inner layer (the inner surface of the container).
5. A medical container having a storage section for storing a medicinal solution, characterized in that at least the storage section is made of the laminate described in claim 2 or 3, and layer A is an inner layer (the inner surface of the container).
6. 6. The medical container according to claim 5, wherein the container portion for containing the liquid medicine is a film-like bag.
7. 6. The medical container according to claim 5, wherein the container for containing the liquid medicine is in the form of a bottle.
8. 8. A medical container according to any one of claims 4 to 7, characterized in that after a sterilization treatment at 126°C, the peel strength of the contact parts of the laminate (between inner layers (the inner surfaces of the container)) is less than 3 N / 15 mm, and the light transmittance measured in pure water at a wavelength of 450 nm is 65% or more.
Citation Information
Patent Citations
Liquid container
JP1995125738A
Retort container
JP1996244791A
Laminate and container made of the same
JP1996309939A
Resin composition and container built of the same
JP2002265705A
Laminate and container
JP2003237002A